Religious conflict in Baghdad during the Buwayhi state in 334-447 AH - Azad Othman Mustafa; Sadraldin Mustafa Qader (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The major problem of the Abbasid Caliphate during the third and fourth periods of the Hijra was the religious problem. Some of the countries that assumed power within the Caliphate worked on religious disputes in the country, and caused the deterioration of the political situation and chaos in the country. The protection of people, the disappearance of markets, the deterioration of trade, and the decline and disappearance of businessmen and the rich because these problems threaten their capital. The primary purpose of the princes was to attack the Sunnis and spread the Shiite doctrine. They discriminated against the people and scholars, and clashes occurred between the Sunnis and the Shiites later, which led to the killing and wounding of many people. People. Another reason for these battles is that the companions of the Prophet were subjected to insults and insults written openly on the walls. The Sunnis attacked Shiite areas, killed each other, and burned each other’s homes. homes and shops. This problem is rooted in Iraq in general and Baghdad in particular, and continues to this day.